2023
DOI: 10.1177/23969873231157884
|View full text |Cite
|
Sign up to set email alerts
|

The association between perihaematomal oedema and functional outcome after spontaneous intracerebral haemorrhage: A systematic review and meta-analysis

Abstract: Purpose: Perihaematomal oedema (PHO) formation has gained increasing interest as a therapeutic target after spontaneous intracerebral haemorrhage (ICH). Whether PHO contributes to poor outcome is unclear. We aimed to determine the association between PHO and outcome in patients with spontaneous ICH. Method: We searched five databases up to 17 November 2021 for studies of ⩾10 adults with ICH reporting the presence of PHO and outcome. We assessed risk of bias, extracted aggregate data and used random effects met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…Some groups have reported that rate of PHE growth is a stronger prognostic factor than baseline PHE volume 19 and that larger PHE is associated with poor functional outcome at 3-months. 15 In our study, the temporal rate and difference of baseline to follow-up CT scans had significant association with outcome but in multivariable analysis correcting for clinical predictors of outcome, they offered no additional prognostic information to baseline PHE volume and sphericity. Although follow-up PHE maximum diameter on axial slices remained as an independent predictor of favorable versus poor outcome in binary logistic regression (Supplemental Table 4), in general, the PHE shape evolution over the first 24 h could barely provide additional prognostic information to baseline variables.…”
Section: Discussioncontrasting
confidence: 58%
“…Some groups have reported that rate of PHE growth is a stronger prognostic factor than baseline PHE volume 19 and that larger PHE is associated with poor functional outcome at 3-months. 15 In our study, the temporal rate and difference of baseline to follow-up CT scans had significant association with outcome but in multivariable analysis correcting for clinical predictors of outcome, they offered no additional prognostic information to baseline PHE volume and sphericity. Although follow-up PHE maximum diameter on axial slices remained as an independent predictor of favorable versus poor outcome in binary logistic regression (Supplemental Table 4), in general, the PHE shape evolution over the first 24 h could barely provide additional prognostic information to baseline variables.…”
Section: Discussioncontrasting
confidence: 58%
“…Future studies should aim to identify if any biomarker is associated with both, since such a biomarker could either be a prognostic marker after ICH or act as an inflammatory mediator which would be more likely to be a potential therapeutic target. Since both animal studies and human studies (of brain tissue and serum) suggest the involvement of inflammatory pathways such as IL-1, HMGB-1, TNF in the perihaematomal region 133 and the development of PHO 126 , and PHO itself is associated with outcome after ICH 134 , 135 , it is plausible that one or more such biomarkers could be involved in the inflammatory response in the brain following ICH.’ Modulating the neuroinflammatory response after ICH, for example by using an IL-1 receptor antagonist (NCT04834388) may therefore hold promise.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies included in meta-analysis reported whether the biomarker helped to improve prediction of prognosis after ICH when compared or added to existing prognostic scores for ICH and this should be examined in future studies. We were unable to explore how variation in PHO measurement between studies affects any association between PHO and prognosis after ICH but this has been discussed elsewhere 134 , 135 .…”
Section: Discussionmentioning
confidence: 99%
“… 6 Perihaematomal oedema (PHO) is considered an important imaging marker of secondary brain injury and is associated with clinical deterioration and worse functional outcome. 7 10 PHO starts to develop during the first 24 h after ICH onset, and continues to increase during the first 7–10 days. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…6 Perihaematomal oedema (PHO) is considered an important imaging marker of secondary brain injury and is associated with clinical deterioration and worse functional outcome. [7][8][9][10] PHO starts to develop during the first 24 h after ICH onset, and continues to increase during the first 7-10 days. 11,12 The pro-inflammatory cytokine interleukin-1 beta (IL-1β) has been identified as an attractive candidate to target secondary brain injury after ICH.…”
Section: Introductionmentioning
confidence: 99%